2009
DOI: 10.20502/rbg.v10i2.126
|View full text |Cite
|
Sign up to set email alerts
|

Apicuns: Aspectos Gerais, Evolução Recente E Mudanças Climáticas Globais

Abstract: ResumoOs apicuns são áreas planas de elevada salinidade ou acidez, localizadas na região de supra-maré e desprovidas de vegetação ou com vegetação rasa; estão necessariamente associados a manguezais e são encontrados nas regiões intertropicais em todo o mundo. Na Baía de Todos os Santos -BTS os manguezais e apicuns ocupam, respectivamente, 177,6 km² e 10,2 km². A distribuição dos apicuns é irregular, não ocorrendo em todas as áreas de manguezais encontradas. A abertura de perfis nos apicuns evidenciou a presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
0
5
0
3
Order By: Relevance
“…Chen et al [54] discuss the relationship between maintaining dune shape and their water content, which contributes to the maintenance of groundwater levels. Other studies, such as carried out by Albuquerque et al [55] and Hadlich and Ucha [56], describe the ecological importance of apicuns flat areas, presenting high salinity or acidity, located in the supramarine region and with shallow or no vegetation, present in intertropical regions and associated with mangroves. These are natural protections for the coastal areas and act against erosion, besides being areas used in recycling nutrients and energy [57].…”
Section: Wind Power and Its Potential Impacts: What Do Studies Saymentioning
confidence: 98%
“…Chen et al [54] discuss the relationship between maintaining dune shape and their water content, which contributes to the maintenance of groundwater levels. Other studies, such as carried out by Albuquerque et al [55] and Hadlich and Ucha [56], describe the ecological importance of apicuns flat areas, presenting high salinity or acidity, located in the supramarine region and with shallow or no vegetation, present in intertropical regions and associated with mangroves. These are natural protections for the coastal areas and act against erosion, besides being areas used in recycling nutrients and energy [57].…”
Section: Wind Power and Its Potential Impacts: What Do Studies Saymentioning
confidence: 98%
“…In Brazil, studies conducted in the apicum facies have revealed the presence of fossil mangroves, indicating that the sea reached higher levels than at present (SORIANO-SIERRA et al, 1998;SAINTILAN;WILLIAMS, 1999;SOARES et al, 2000;SCHAEFFER-NOVELLI et al, 2002;BEHLING et al, 2004;COHEN et al, 2005;STEVENS et al, 2006;SOARES, 2009;HADLICH;UCHA, 2009;FRIESS et al, 2012).…”
Section: Sea Level Risementioning
confidence: 99%
“…Abordam sua relação como local para a carcinicultura (CREPANI; MEDEIROS, 2003;SANTOS, 2005). Realizam análise espaço temporal do ambiente (JESUS; UCHA, 2009;SANTANA et al, 2010). E o caracterizam (SANTOS et al, 1996;SCHAEFFER-NOVELLI, 1999;SUSILO, 2005;UCHA, 2009), em estudos granulométricos do sedimento (PELLEGRINI, 2000;HADLICH et al, 2008), além de micro-topografia, salinidade e caracterização vegetal da área (PELLEGRINI, 2000;SIQUEIRA, 2009).…”
Section: Introductionunclassified
“…Realizam análise espaço temporal do ambiente (JESUS; UCHA, 2009;SANTANA et al, 2010). E o caracterizam (SANTOS et al, 1996;SCHAEFFER-NOVELLI, 1999;SUSILO, 2005;UCHA, 2009), em estudos granulométricos do sedimento (PELLEGRINI, 2000;HADLICH et al, 2008), além de micro-topografia, salinidade e caracterização vegetal da área (PELLEGRINI, 2000;SIQUEIRA, 2009). Dentre os trabalhos citados, apenas Pellegrini (2000), determinou teores de matéria orgânica e de carbonatos e Nascimento (1993), estudou apenas o primeiro parâmetro.…”
Section: Introductionunclassified